Some reservations regarding the use of artificial intelligence applications in the peer review process of scholarly publications - Bahşi, İlhan; Durna, Yusuf Muhammed; Tekin, Mustafa Said; Duymaz, Yaşar Kemal (My University, 2024)
...
Keywords: Surgery; Letter; Scholarly Publications